Artemisia vulgaris L. supplementation on development, mortality, and hatching rate of Zebrafish embryo exposed to heat stress during in vitro culture - Tuska, Habib Syaiful Arif Tuska; Farida Puspita Zuhria; Bonick Kartini Lonameo; Muhammad Arfan Lesmana (Veterinary Biomedical and Clinical Journal, 2025)
We investigated the effect of Artemisia vulgaris L. supplementation on Zebrafish embryos exposed to heat stress during in vitro culture. Zebrafish embryos were divided into two groups, namely heat stress (HS; 36oC) and non-heat stress or control (NHS; 28oC), with each group was given three different doses of Artemisia (0µL=P1, 2µL=P2, and 4µL=P3; 4 replicates). Zebrafish embryos were evaluated periodically every three hours up to 48 hpf (hour post-fertilization), and five hours up to 96 hpf. Data obtained was analyzed using SPSS, One-Way ANOVA. It showed that Zebrafish embryos’ development under heat stress conditions without Artemisia experienced delays in the neurula, organogenesis, and hatching phases. The mortality rate in HS P3 (5±5%; least square means±standart error) was lower (P<0,05) compared with NHS P1 (7.5±4.8%). The highest average hatching rates were found in NHS P3 (4µL) (85±9.6%) and HS P3 (4µL) (75±6.5%). It showed that Artemisia has an ability to reduce mortality rate and increase the hatchability of Zebrafish embryos exposed to heat stress.